Risk Assessment and Accumulation of Metals in Sediment of Koycegiz Lagoon System, Turkey - GENC, Tuncer Okan; YILMAZ, Fevzi (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
This paper focuses on metal (Cr, Cu, Pb, Mn and Zn) accumulation and degree of contamination in the sediments of the Koycegiz Lagoon Systems. Pollution by these metals was examined using several calculation methods: pollution load index (PLI), contamination factor (CF), geoaccumulation index (lgeo) and enrichment factors (EF). The mean value of contamination factor (CF) for Pb, Cu, Zn, Mn metals showed low degree of contamination (CF < 1), whereas Cr showed considerably degree (3CF< 6). Higher PLI values were observed in sampling sites III where discharge point of waste water and the PLI values indicated that Cr is the major contributors to the sediment pollution. Average lgeo values of analyzed metals (except Cr) indicating uncontaminated to moderately contaminated status of the sediment whereas the Igeo values for Cr indicates moderately to strongly contaminated status. For most of the sites EF of the studied metals were lower than 1 indicating there is not intense human influence to the metal pollution in sediments.